Influence of Professionalism, Teaching media, and Literacy on the Merdeka Curriculum through the Creativity of Junior High School Teachers - Erni Ratna Dewi; Andi Aminullah Alam (Universitas Negeri Makassar, 2024)
The study aims to analyze the influence of professionalism, teaching media, and literacy on the Merdeka curriculum through teachers' creativity. This is a quantitative study purposively involving 236 Junior High School teachers in Tamalanrea district. The data collection technique was a questionnaire, literature review, and observation. Data were analyzed using SEM analysis with the SmartPLS technique. The findings show that professionalism, teaching media, and literacy influence the Merdeka curriculum. It means that they have a positive and significant influence on the Merdeka curriculum. Professionalism and teaching media positively and significantly influence teacher's creativity. On the other hand, literacy does not significantly influence teachers' creativity. Professionalism and teaching media positively and significantly influence teacher's creativity. Professionalism positively and significantly influences the Merdeka curriculum through teachers' creativity as a mediating variable. Teaching media and literacy positively and significantly influence performance through teachers' creativity as a mediating variable.